Predicting response to pembrolizumab in metastatic melanoma by a new personalization algorithm - Tsur, Neta; Vogler, Nils; Utikal, Jochen (Journal of translational medicine, 2019)
At present, immune checkpoint inhibitors, such as pembrolizumab, are widely used in the therapy of advanced non-resectable melanoma, as they induce more durable responses than other available treatments. However, the overall response rate does not exceed 50% and, considering the high costs and low life expectancy of nonresponding patients, there is a need to select potential responders before therapy. Our aim was to develop a new personalization algorithm which could be beneficial in the clinical setting for predicting time to disease progression under pembrolizumab treatment.